2000
DOI: 10.2307/3454434
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Tibial Lead Levels with BsmI Polymorphisms in the Vitamin D Receptor in Former Organolead Manufacturing Workers

Abstract: We evaluated associations of tibial lead levels with polymorphisms in the vitamin D receptor (VDR) in 504 former organolea manauri workers with past exposure to lead. In this crosssectional study, we measured tibia! lead by 109Cd K-shell X-ray fluorescence. Tibial lead was evaluated in subjects with different VDR genotypes defined using the BsmI restriction enzyme,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…First, genetic polymorphism of VDR has been associated with susceptibility to Pb and vitamin D deficiency in some studies; e.g. the VDR FokI (rs2228570) f genotype was associated with high 25(OH)D level and low blood Pb (22,23,(40)(41)(42) , which indicates that genetic features are not to be ignored. Second, some studies in animals have demonstrated that relationships among Pb, dietary Ca and vitamin D are complex and in some cases counterintuitive, and therefore are not predictable based solely on theoretical considerations (43)(44)(45) .…”
Section: Discussionmentioning
confidence: 99%
“…First, genetic polymorphism of VDR has been associated with susceptibility to Pb and vitamin D deficiency in some studies; e.g. the VDR FokI (rs2228570) f genotype was associated with high 25(OH)D level and low blood Pb (22,23,(40)(41)(42) , which indicates that genetic features are not to be ignored. Second, some studies in animals have demonstrated that relationships among Pb, dietary Ca and vitamin D are complex and in some cases counterintuitive, and therefore are not predictable based solely on theoretical considerations (43)(44)(45) .…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe associations between the 3 lead biomarkers and VDR and APOE genotypes, in contrast to findings from occupational studies. 38,54 This may be because of lower concentrations of lead in all tissues in nonoccupational studies. However, in adjusted analysis of patella lead concentrations, there was evidence of effect modification by APOE genotype on relations of gender with patella lead concentrations.…”
Section: Differences By Agementioning
confidence: 99%
“…Creatinine in urine was analyzed by the Sigma kit (St. Louis, Missouri, United States) (33). ALAD and VDR genotyping were completed for 798 exposed subjects and 795 referents by previously described methods (34)(35)(36)(37).…”
Section: Laboratory Methodsmentioning
confidence: 99%